EVALUATION OF GENTAMICIN DOSES FOR TREATING CHILDREN WITH SEVERE PNEUMONIA - Nialiana Endah Endriastuti; Djoko Wahyono; Ristantio Sukarno (Faculty of Pharmacy, Universitas Gadjah Mada)
Administration of gentamicin in pediatric with severe pneumonia cases is a rational use of antibiotic. Gentamicin as a narrow therapeutic range agent (0.5 to 10 mg/L) should be followed by monitoring using TDM in order to know the levels of drug in the patient’s body so it does not cause toxicity or effects of drugs that are too small. This study aimed to estimate levels of gentamicin in serum after administration pediatric with pneumonia at Dr. Sardjito Hospital and assesed the improvement of clinical outcomes.The study was conducted retrospectively and data were obtained from medical record of pediatric inpatient, 1 month-16 years, whose recieved gentamicin in Dr. Sardjito Hospital in period between January 2009-April 2014. Clinical outcomes were namely body temperature, respiratory rate, chest retraction, and leucocyte number. The data were analyzed descriptively including the patient characteristics, estimated blood levels of gentamicin, estimated gentamicin for adjusment dose. In order to determine the effect of clinical outcome parameter on the success of therapy. Data were analyzed statistically using chi square on SPSS program. The results showed that the average of blood levels of gentamicin in all 31 patients were in therapeutic range (0.5 to 10 mg/L). However there were 20 patients (64,52%) had the level of gentamicin at > 10 mg/L and 10 patient (32,26%) had < 0,5 mg/L. The research also showed that 8 patient had improvement in the clinical outcome although 23 patient not yet had improvement in these parameters.Keywords: severe pneumonia, gentamicin, dose evaluation, estimate levels, clinical outcome